Formulation and Characterization of Sodium Caseinate/Phloretin Complexes as Antioxidant Stabilizers in Oil-in-Water Emulsions - Najme Kheynoor; Jean-Christophe Jacquier; Mohammadreza Khalesi; Amir Mohammad Mortazavian; Mohammad-Taghi Golmakani (Foods)
Emulsifiers with antioxidant properties, such as protein/polyphenol complexes, adsorb at the oil-water interface and improve the physical and oxidative stability of emulsions. Here, 2% (w/w) sodium caseinate and varying concentrations of phloretin (0–10 mM) were used to stabilize oil-in-water emulsions. Control emulsions with protein alone showed poor stability with increased droplet sizes from 0.33 µm to 5.18 µm after 30 days, while no significant change was observed in emulsions containing phloretin (remaining below 400 nm). The in vitro antioxidant activities increased with increasing phloretin concentrations (0 to 10 mM). In the ABTS assay, the antioxidant activity improved from 14.02 ± 8.33% to 95.09 ± 1.31%, and in the DPPH assay, it increased from 32.59 ± 2.73% to 99.03 ± 0.14%. Similarly, the oxidative stability of the emulsions improved with increasing phloretin concentrations (0 to 10 mM). After 30 days of storage, PV decreased from 38.22 ± 2.58 µM to 11.81 ± 2.55 µM, and MDA content reduced from 48.43 ± 0.31 µM to 7.24 ± 0.21 µM. Measuring the apparent viscosity demonstrated a reduction in viscosity with the addition of phloretin. These findings demonstrate that incorporating phloretin into sodium caseinate-stabilized emulsions as a novel antioxidant emulsifier can be an effective strategy to extend the shelf life of emulsified food products prone to oxidative deterioration.